Projeto de rebranding Maria Gambina - Pombares, Rui (2014)
Submitted by Sara Pereira (sarapereira@esad.pt) on 2014-02-17T11:22:30Z No. of bitstreams: 12 01_Paginas_Institucionais.pdf: 40685875 bytes, checksum: 603c8fa3c6725391e60fd95cc3a784d5 (MD5) 02_Introducao.pdf: 27156077 bytes, checksum: 7e4918ee15b70793659ade67e84a69f4 (MD5) 03_ET_1Marca.pdf: 91104631 bytes, checksum: 8010ce1d1f24964b382c698dfaa52205 (MD5) 04_ET_2Design_e_Marca.pdf: 31481957 bytes, checksum: 18b92e310f32a00a8c2578d6276b0140 (MD5) 05_ET_3Idenidade_Marca.pdf: 75189164 bytes, checksum: 871198c8c0c3343fc05ef55ab2a4dfea (MD5) 06_ET_4ModeloDiagnostico.pdf: 48184688 bytes, checksum: 468848dd4f797f297f9d9bcd1524339b (MD5) 07_P_1Objetivos.pdf: 71253514 bytes, checksum: 65368dd007628ec4bfe85d9cd9f051ca (MD5) 08_P_2Metodologia.pdf: 36359368 bytes, checksum: 24e81a4032d25f803e885158740f6cf1 (MD5) 09_P_3DiagnosticoMG.pdf: 13561413 bytes, checksum: 74419afa1c25fab8ddada4e40638ad98 (MD5) 10_P_4RedefinicaoMG.pdf: 16829615 bytes, checksum: d9f2d4ed6a7b60267cae221cf4c7958c (MD5) 11_ConsideracoesFinais.pdf: 4370138 bytes, checksum: e8a6c35ab8a8dfcd04af8cfeec1cb63a (MD5) 12_Bibliografia.pdf: 879304 bytes, checksum: f7d7c9487db222ee6bae05ac544f0429 (MD5)